Systematic evaluation of velocity‐selective arterial spin labeling settings for placental perfusion measurement - Harteveld, Anita A.; Hutter, Jana; Franklin, Suzanne L.; Jackson, Laurence H.; Rutherford, Mary; Hajnal, Joseph V.; Osch, Matthias J. P.; Bos, Clemens; De Vita, Enrico (Magnetic resonance in medicine, 2020)
Purpose Placental function is key for successful human pregnancies. Perfusion may be a sensitive marker for the in vivo assessment of placental function. Arterial spin labeling (ASL) MRI enables noninvasive measurement of tissue perfusion and it was recently suggested that ASL with velocity‐selective (VS) labeling could be advantageous in the placenta. We systematically evaluated essential VS‐ASL sequence parameters to determine optimal settings for efficient placental perfusion measurements. Methods Eleven pregnant women were scanned at 3T using VS‐ASL with 2D multislice echo planar imaging (EPI)‐readout. One reference VS‐ASL scan was acquired in all subjects; within subgroups the following parameters were systematically varied: cutoff velocity, velocity encoding direction, and inflow time. Visual evaluation and region of interest analyses were performed to compare perfusion signal differences between acquisitions. Results In all subjects, a perfusion pattern with clear hyperintense focal regions was observed. Perfusion signal decreased with inflow time and cutoff velocity. Subject‐specific dependence on velocity encoding direction was observed. High temporal signal‐to‐noise ratios with high contrast on the perfusion images between the hyperintense regions and placental tissue were seen at ~1.6 cm/s cutoff velocity and ~1000 ms inflow time. Evaluation of measurements at multiple inflow times revealed differences in blood flow dynamics between placental regions. Conclusion Placental perfusion measurements are feasible at 3T using VS‐ASL with 2D multislice EPI‐readout. A clear dependence of perfusion signal on VS labeling parameters and inflow time was demonstrated. Whereas multiple parameter combinations may advance the interpretation of placental circulation dynamics, this study provides a basis to select an effective set of parameters for the observation of placenta perfusion natural history and its potential pathological changes.